COVID‐19 and future pandemics: is isolation and social distancing the new norm?. Issue 5 (6th May 2021) - Collignon, Peter
Abstract: The coronavirus, named SARS‐CoV‐2, is the cause of COVID‐19. This virus spreads readily from person to person and predominantly to and from the respiratory route and through droplets. There are many different interventions that can be and are used to decrease successfully the risk and spread of COVID‐19. Most of the principles underpinning these interventions relate to isolation and social distancing. These will need to be continued, at least in part, until safe and very effective vaccines become widely available and are delivered extensively and successfully globally. This new norm is isolation, plus social and physical distancing, and this new norm will likely be with us for some time to come. It will also be with us in any future pandemics, whether caused by bacteria or viruses, but especially when the causative pathogen spreads predominantly through the respiratory route. However, lockdowns and restrictions also cause many adverse but unintended economic, social and health consequences. Therefore, what is put into place needs to be proportionate to levels of risk of disease as well as spread, and which will vary in different localities and with time.